Why Should The Death Penalty Not Be Abolish For Narcotics Crimes? A Case Study In Indonesia - Rafsanjani, Ony; Mustaffa, Aminuddin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Narcotic crimes are global phenomena that transcend jurisdictional borders. In Indonesia, narcotics crimes attract a different form of punishment, including the death penalty, depending on the nature and gravity of the crimes. This study examines Indonesian law’s death penalty sentence for narcotics crimes. It explores the governing principles and current law position relating to this controversial law. This research adopts doctrinal research. The sources of legal materials consist of three, namely, primary, secondary, and tertiary sources of law. The results of this study reveal that the death penalty for the offenders of narcotics crimes under Indonesian law is lawful and justifiable, considering its gravity, nature and impacts. The crimes have caused substantial social, economic and resource loss to the nation and country.